(untitled) (European Journal of Marketing and Economics, 2020)
The study measures the relationships of pay satisfaction and its dimensions (pay level, benefits, pay raises and administration/structure) with job satisfaction. A total of 200 public sector employees, from different companies and non-governmental, independent institutions participated. The results showed that overall pay satisfaction and pay level affected job satisfaction while pay raises, benefits and administration/structure did not. The results and limitations of the study were discussed and suggestions on future research were given.